Targeting COVID-19 vaccine hesitancy among nurses in Shanghai: A latent profile analysis - Zhang, Enming; Dai, Zhengyue; Wang, Caifeng; Hu, Jiale; Wang, Suxing; Zhang, Lin; Fang, Qiong (Frontiers in Public Health, 2022)
Objectives： This study aims to clarify the profiles of the psychological antecedents of vaccine hesitancy among Shanghai nurses with a person-centered approach. Methods： A population-based cross-sectional online survey was conducted on Shanghai nurses from July to August 2021 (N=1928). In the online survey, participants were asked to report their sociodemographic, the 5C vaccine hesitancy components, their knowledge level of COVID-19 vaccine and vaccination, and the COVID-19 vaccination uptake intention and attention to vaccine news. Latent profile analysis was used to reveal distinct profiles of vaccine hesitancy. Results： Results revealed four profiles, including “believers” (68.9%; high confidence and collective responsibility), “free-riders” (12.7%; similar characteristics to believers, except for a low collective responsibility), “middlemen” (14.6%; middle in all 5C constructs), “contradictors” (3.7%; high in all 5C constructs). Compared to believers, middlemen were younger, more likely to be female, childless, less educated, held lower professional titles, had fewer years of nursing service, sometimes or never complied with recommended vaccinations, had satisfactory or poor self-assessed health status, had no work experience during the COVID-19 epidemic, and possessed greater levels of knowledge. Free riders were more likely to work in community health centers and have a lower degree than believers. Contradictors were more likely to work in community health centers, had junior college degrees or lower, and had no work experience during the COVID-19 epidemic than believers. From the highest to the lowest on vaccination intention and attention to vaccine news were believers, then free riders, contradictors, and finally middlemen. Conclusion： This study could aid in the development of personalized vaccination strategies based on nurses’ vaccine hesitancy profiles and predictors. In addition to vaccine believers, we identified other three profiles based on their 5C psychological antecedents, emphasizing the significance of establishing tailored vaccination campaigns. Further research into the prevalence of profile structure in other groups of healthcare workers is required.